Handbook of Pathogens and Diseases in Cephalopods 2019
DOI: 10.1007/978-3-030-11330-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Affecting Cephalopods

Abstract: Bacterial pathogens contribute to obtain an unsuccessful production of cephalopods. An updated overview of the knowledge of these pathogens must be a valuable tool to improve their aquarium maintenance and aquaculture. The present work provides a description of the main bacterial pathogens associated with larval stages of cultured Octopus vulgaris, and juvenile and adults of several cephalopods. Vibrio species, reported with ability to cause vibriosis in aquaculture, are the main bacteria associated with skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…11,16 Epitheliocystis-like lesions (ELLs) have been infrequently described in octopuses, in which they have been considered to be Rickettsia-like organisms (RLOs) based on histomorphology but have not been characterized at a molecular level. 21,27 Similar infections were found in 3.2% of study octopuses and were consistently located in the gill epithelial cells. Comparatively, histomorphologically similar Rickettsia or Chlamydia-like organisms in mollusks have been identified as gammaproteobacterial-Endozoicomonadaceae.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…11,16 Epitheliocystis-like lesions (ELLs) have been infrequently described in octopuses, in which they have been considered to be Rickettsia-like organisms (RLOs) based on histomorphology but have not been characterized at a molecular level. 21,27 Similar infections were found in 3.2% of study octopuses and were consistently located in the gill epithelial cells. Comparatively, histomorphologically similar Rickettsia or Chlamydia-like organisms in mollusks have been identified as gammaproteobacterial-Endozoicomonadaceae.…”
Section: Discussionsupporting
confidence: 73%
“…During the period May 2003 to August 2022, 593 cephalopod submissions representing 22 species from 4 orders (Octopoda, Sepiida, Sepiolida, and Nautilida) were submitted. Common octopus (193), European common cuttlefish (90), hummingbird bobtail squid (21), and chambered nautilus (89) were the most numerous species (Table 1 and Supplemental Table S1). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most common bacterial, fungal, and parasitic infectious agents causing systemic diseases in octopuses are Vibrio sp., Labyrinthulomycetes, and Aggregata sp., respectively. [29][30][31] Skin lesions are seen in octopuses with Vibrio and Labyrinthulomycetes infections, but only the former is known to also colonize the eyes, while Photobacterium swingsii and Lactococcus garvieae have been associated with retrobulbar lesions in the octopus. 30,31 Octopus #1 had clusters of coccidal parasites, identified as Aggregata sp., in its extraocular blood vessels and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that healthy octopuses and squids are associated mainly with Vibrio sps followed by members of other genera such as Pseudomonas, Aeromonas, Staphylococcus or Streptococcus sps. 27 . The presence of Stenotrophomonas sp., Alcaligenes sps, Pseudomonas sps, and Myroides sps require detailed study to assess their role as opportunistic pathogens that can affect human life or probable probiotics, or in bioremediation, production of antibiotics or other industrial uses 28,29 .…”
Section: Extraction and Identification Of Proteinsmentioning
confidence: 99%